8x-4y-6y+5x+10=

Simple and best practice solution for 8x-4y-6y+5x+10= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-4y-6y+5x+10= equation:


Simplifying
8x + -4y + -6y + 5x + 10 = 0

Reorder the terms:
10 + 8x + 5x + -4y + -6y = 0

Combine like terms: 8x + 5x = 13x
10 + 13x + -4y + -6y = 0

Combine like terms: -4y + -6y = -10y
10 + 13x + -10y = 0

Solving
10 + 13x + -10y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + 13x + -10 + -10y = 0 + -10

Reorder the terms:
10 + -10 + 13x + -10y = 0 + -10

Combine like terms: 10 + -10 = 0
0 + 13x + -10y = 0 + -10
13x + -10y = 0 + -10

Combine like terms: 0 + -10 = -10
13x + -10y = -10

Add '10y' to each side of the equation.
13x + -10y + 10y = -10 + 10y

Combine like terms: -10y + 10y = 0
13x + 0 = -10 + 10y
13x = -10 + 10y

Divide each side by '13'.
x = -0.7692307692 + 0.7692307692y

Simplifying
x = -0.7692307692 + 0.7692307692y

See similar equations:

| -4x+.66=2.3 | | x-5/2-6=x-4/3 | | m/15=9/32 | | -5x^2-14+x^4=0 | | 4x-5(5-x)= | | (-4y+4)-(-3y-8)=2 | | (8+2)(7+(2+4))=X | | V=LWHfrow | | 7-3(5-10)=67 | | (8+2)(7+(2+2))=X | | (5/11)(6) | | 24x+9=18x+3 | | 3x/3=a-1/3 | | t=(.20+2.15)873.36 | | 2x/3-7=5 | | 8x^2+18x-15=20 | | t=(.15+2.15)873.36 | | -4-22v+8=6-6-9v+6v | | 3(5-3v)+9v=28 | | (5x-2)(6x+3)= | | t=(.1+2.15)873.36 | | 10(z+4)-2(z-2)=3(z-2)+4(z-1) | | -32-9y=23 | | 27/21=X/28 | | x^2+128x-256=0 | | t=(.10+2.15)873.36 | | (8x^2-3x^3)-(2x^2-7x^3)= | | t=(0.010+2.15)873.36 | | -16-9y=-24 | | x^3+30x^2-400=0 | | 16-9y=-24 | | 2b=-0.6 |

Equations solver categories